THE LINK BETWEEN INTERPERSONAL VIOLENCE AND ANIMAL ABUSE - VINCENT, AVIVA; MCDONALD, SHELBY; POE, BETHANIE; DEISNER, VICKI (Society Register, 2019)
In 2018, more homes in the US have pets than those that have children. Though pets are regarded as property by US law, a majority of people identify pets as part of the family unit. Animal abuse and cruelty have been identified as a potential indicator and precursor to interpersonal violence (IPV). Moreover, child maltreatment, domestic violence, elder abuse, and animal abuse co-occur in households and communities link together to indicate the nexus of these heinous crimes; these co-occurring forms of violence have been increasingly referred to as The Link, to indicate the linked violence. However, there is an incongruence in the definition of animal abuse and cruelty; thus, documenting cases, bringing charges, and achieving a conviction is difficult. Furthermore, the initial education to learn of these topics in human service professions, such as social work, remains absent from many curricula. In practice, cross-reporting of suspected abuse or neglect is a vital mechanism for connecting human and animal professionals to address the issues between human and animal welfare systems. This sharing of information can increase the likelihood that clients experiencing IPV will receive comprehensive services that can improve their level of safety and quality of life. By providing professionals with education for indicators of abuse, and strategies for how to make a report, communities can build stronger support networks for those in need. Herein, Ohio legislation and current community efforts serve as a case study to define animal abuse, delineate transdisciplinary factors for relevance, and make recommendations for addressing this vital social welfare need. The strategies within this case-study are encouraged to be adapted and applied nationally and internationally.